2011
DOI: 10.4103/1119-3077.91758
|View full text |Cite
|
Sign up to set email alerts
|

Use of information and communication technology among dental students and registrars at the faculty of dental sciences, University of Lagos

Abstract: The aim of this study was to investigate the use of information technology amongst dental students, dental nursing students and resident doctors in training at the faculty of dental Surgery University of Lagos. A structured questionnaire was distributed to 58 clinical dental students in 4 th and 5 th years of training in the 2010/2011 academic year, 36 dental nursing students and 63 resident doctors undergoing specialist training. All participants have access to the computers, 2.5% within the University and 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…( 20 ) Glinkowski, Pawlowska and Kozlowska discovered that the definition of tele-medicine was known by 82% of nursing students in Poland. However, in our study, 32.3% of medical students had good knowledge, while 50% showed good practice patterns which were in compliance with other findings ( 13 , 14 , 18 ). In a study by Manganello et al, it was found that the use of HIT had a direct correlation with the level of health education, whereas the higher use of HIT was related to higher health education and the lower use of HIT was related to lower health education ( 22 ) Generally, the level of knowledge and attitude should be higher than the level obtained in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…( 20 ) Glinkowski, Pawlowska and Kozlowska discovered that the definition of tele-medicine was known by 82% of nursing students in Poland. However, in our study, 32.3% of medical students had good knowledge, while 50% showed good practice patterns which were in compliance with other findings ( 13 , 14 , 18 ). In a study by Manganello et al, it was found that the use of HIT had a direct correlation with the level of health education, whereas the higher use of HIT was related to higher health education and the lower use of HIT was related to lower health education ( 22 ) Generally, the level of knowledge and attitude should be higher than the level obtained in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Glinkowski, Pawlowska and Kozlowska have surveyed the perception and knowledge of tele-health and tele-nursing among university students of nursing in Poland ( 17 ). In addition, the study of Butali et al was on the use of IT among dental students and resident physicians ( 18 ). In a case in 2015, Baraka et al assessed the acceptance and knowledge of IT in health care practice ( 19 ), while Sinha and Shetty studied the attitude of physicians towards the efficiency of HIT in Ayurveda educational hospital ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over half the dental students in our study reported that internet and electronic resources can replace print resources in contrast with the Indian dental students (Manhas, 2008) where the majority felt that the Internet and electronic resource could only supplement the print resources. The majority of the students in the current study were confident in the accuracy and the relevance of information from the internet and was similar to the findings of Nigerian dental students (Butali et al, 2011).The dental students in this study graded their basic PC skills higher than their search skills corresponding with the findings of dental students in Finland (Romanov and Aarnio, 2006).…”
Section: Percentagesupporting
confidence: 81%
“…Among different institutions, only 28% of the health facilities which was very low as compared to other institution used computer for different purposes [4]. In contrary, there was high knowledge and use of computers among dental sciences faculty, at the University of Lagos, Nigeria [5]. …”
Section: Introductionmentioning
confidence: 99%